Assessing the impact of FoxP3 and Vav1 gene polymorphisms on kidney allograft survival - Adamek, Martina Maria; Döhler, Bernd; Fiedler, Gerd; Scherer, Sabine; Opelz, Gerhard; Tran, Thuong Hien (HLA, 2017)
FoxP3 and Vav1 are known to be involved in the development of regulatory T cells. Two polymorphic sites in the FoxP3 promoter (rs3761548 and a (GT) n -dinucleotide repeat) and 2 single nucleotide polymorphisms in intron 1 of the Vav1 gene (rs2546133 and rs2617822) have been shown to correlate with gene expression levels. We investigated a potential impact of FoxP3 and Vav1 genetic variants on kidney allograft failure using samples and data of the Collaborative Transplant Study. A cohort of 384 kidney transplant patients was tested. We found no significant association of FoxP3 promoter rs3761548 or (GT) n repeat length with presumed immunological graft failure. The genotype frequencies of Vav1 intron polymorphisms did not significantly differ between patients with graft failure and matched controls.
First published: 03 May 2017
Gesehen am 22.10.2018